Preaching about the Holy Trinity: Inspiration from Pope Francis - Popo, Frederick Ray (Journal of Asian Orientation in Theology, 2025)
Every year, there is one Sunday to celebrate the Solemnity of the Most Holy Trinity. This means that every year, priests have the opportunity to give a homily or sermon in order to explain for their flock the meaning of the Triune God. With a 10-minute time limit for homilies set by Pope Francis, it is important for preachers to find a balance between simple delivery and rich theological reflection. How to do it? This research analyzes Pope Francis' sermons and homilies on the Solemnity of the Holy Trinity, over a period of 10 years (2013-2023), to understand how the Pope offers a theological synthesis of the Triune God concept. This research consists of three parts: collecting and reading the Pope's sermon as primary data, processing and analyzing it in-depth, then finally figuring out the theological influences to the Pope's views and teachings about the Holy Trinity, especially Ignatian spirituality. This research shows that Pope Francis offers a balanced and easy-to-understand reflection on the Triune God, Christology, and soteriology. From the Pope's sermons, preachers are reminded to ensure a grounded experience of the Trinity in the lives of the faithful, making the theological concept transformative and at the same time relevant.